Preparation method of xylem-derived array type through pore channel structure hard carbon negative electrode material

By controlling the pyrolysis parameters, a xylem-derived array-type through-channel structure hard carbon material was prepared, which solved the problems of low efficiency and complex preparation of existing hard carbon materials in sodium ion batteries, achieved high capacity and excellent rate performance, and promoted the Commercial application of sodium ion batteries.

CN119390041APending Publication Date: 2025-02-07YANGZHOU UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411009186.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing hard carbon materials face problems such as low initial Coulomb efficiency, poor ion diffusion kinetics, complex preparation process and high cost in sodium ion batteries, which affect their actual capacity and commercial application.

Method used

By controlling the pyrolysis temperature and heating rate, a xylem-derived array through-hole structure hard carbon anode material was prepared, accurately regulated the microstructure of graphite, maintained the three-dimensional porous form, simplified the preparation process and reduced costs.

Benefits of technology

The high capacity, excellent rate performance and high initial Coulomb efficiency of hard carbon anode materials have been achieved, which significantly improves the electrochemical performance of sodium ion batteries and promotes its commercial application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390041A_ABST
    Figure CN119390041A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a xylem-derived array type through-pore structure hard carbon negative electrode material, which comprises the following steps: crushing plant xylem, washing to remove impurities, and drying to obtain a hard carbon precursor; under the protection of inert gas, the hard carbon precursor is heated to 550-700 DEG C for pre-carbonization treatment for 2-3 h, and a xylem precursor is obtained; under the protection of inert gas, the xylem precursor subjected to pre-carbonization treatment continues to be heated to 1200-1450 DEG C, heat preservation and high-temperature pyrolysis are conducted for 1-3 h, the array pore channel structure hard carbon material is obtained after washing and drying, and the heating temperature rise speed is 2-5 DEG C / min. The hard carbon negative electrode material disclosed by the invention shows excellent first effect and rate capability. The preparation method disclosed by the invention is simple and feasible in process, wide in raw material source and low in cost, and the obtained hard carbon negative electrode material has the advantages of high capacity, excellent rate capability, high initial coulombic efficiency and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy batteries, and in particular relates to a negative electrode material suitable for sodium ion batteries and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have been widely studied and applied due to their excellent electrochemical properties. However, with the advent of the era of electric vehicles and intelligent power grids, market demand is expanding, and the shortage of lithium resources (0.065% in the earth's crust) has become an important factor restricting its development.

[0003] Sodium-ion batteries and lithium-ion batteries have the same working principle and similar battery structure. At the same time, due to the abundant sodium resources (2.75% content in the earth's crust), wide regional distribution, low cost, safety and environmental protection, and excellent comprehensive performance, sodium is suitable for large-scale application to partially replace lithium-ion batteries and alleviate the market's excessive dependence on lithium resources. A new energy storage system. At present, the commercial electrode materials of the existing lithium battery system are not applicable to the sodium-ion battery system. Finding suitable positive and negative electrode materials is particularly important for the development of sodium-ion batteries. As for the negative electrode, hard carbon has become the most promising candidate material for sodium-ion batteries due to its abundant resources, low cost, and excellent sodium storage performance. However, hard carbon still faces key problems such as low initial coulomb efficiency (ICE) and poor ion diffusion kinetics that need to be solved, which greatly affects the actual capacity of hard carbon, especially under high current density conditions.

[0004] The electrochemical properties of hard carbon are mainly affected by its microstructure. The pyrolysis parameters play a decisive role in the change of its microstructure. However, the traditional preparation methods of hard carbon materials often have problems such as difficult to accurately control the microstructure and complex preparation process. Studies have shown that sodium ions can only be freely inserted or removed in carbon layers with a spacing of 0.36nm-0.40nm. Therefore, the pseudo-graphite structure has the most significant effect on the capacity of hard carbon. Adjusting the carbonization temperature can promote the evolution of its structure and the formation of pseudo-graphite structure, thereby increasing the capacity of the low-pressure zone. However, higher carbonization temperatures cause the pseudo-graphite domains to continue to evolve into graphite-like domains, and the graphite-like layers with narrow spacing will lose their sodium storage capacity, resulting in reduced capacity.

[0005] Patent CN1422235A discloses a method for preparing a hard carbon precursor by liquid phase dehydration of resin in an autoclave, but the preparation process of this method is cumbersome and the cost of the precursor is high, which is not suitable for industrial production. Patent CN103311519A discloses a method for preparing a composite hard carbon material by cross-linking polymerization of asphalt. The preparation process is relatively simple, but there are still problems such as low initial coulomb efficiency. Summary of the invention

[0006] Purpose of the invention: The present invention takes improving the first efficiency and rate performance of existing hard carbon negative electrodes as its starting point, while taking into account solving the core problems such as complex preparation process, high manufacturing cost, and difficulty in commercialization. A method for preparing a xylem-derived array-type through-pore structure hard carbon negative electrode material is proposed. The present invention can accurately regulate the microstructure of graphite by controlling parameters such as pyrolysis temperature and heating rate. At the same time, the prepared hard carbon can well retain the xylem array-type through-pore morphology, thus showing excellent first efficiency and rate performance. The preparation method of the present invention is simple and easy, the raw material source is wide and the cost is low, and the obtained hard carbon negative electrode material has the advantages of high capacity, excellent rate performance, and high initial coulombic efficiency.

[0007] Technical solution: To achieve the above invention purpose, the present invention adopts the following technical solution: A method for preparing a xylem-derived array-type through-hole structure hard carbon negative electrode material, comprising the following steps:

[0008] S1, after the plant xylem is crushed, it is washed to remove impurities and dried to obtain a hard carbon precursor;

[0009] S2, under the protection of inert gas, heating the hard carbon precursor to 550-700° C. for pre-carbonization treatment for 2-3 hours to obtain a xylem precursor, wherein the heating rate is 2-5° C. / min;

[0010] S3, under the protection of inert gas, the pre-carbonized wood precursor is further heated to 1000-1400°C and pyrolyzed at high temperature for 1-3 hours, and after washing and drying, a hard carbon material with an array pore structure is obtained, and the heating rate is 2-5°C / min.

[0011] Furthermore, in steps S1 and S2, the inert gas is high-purity argon gas with a flow rate of 0.2 to 0.4 L / min.

[0012] Furthermore, the plant wood is made of paulownia, sycamore, elm or maple.

[0013] Furthermore, the washing in step S1 is performed by alternately washing with deionized water and anhydrous ethanol for at least 3 times; and the washing in step S3 is performed by alternately washing with 1 mol / L HCl solution and deionized water for at least 2 times.

[0014] Furthermore, the temperature of the drying treatment in steps S1 and S3 is 70-85°C, and the drying time is at least 12 hours. The present invention also provides a method for preparing a negative electrode sheet for a sodium ion battery, comprising the following steps: mixing and stirring the hard carbon negative electrode material prepared by any of the methods described in claims 1 to 5, an adhesive and a conductive agent in a mass ratio of 8:1:1, and grinding to form a paste slurry, applying the paste slurry on a current collector substrate by a doctor blade method, and vacuum drying at a temperature of 70-120°C for 1-6 hours.

[0015] Furthermore, the coating amount of the paste slurry on the current collector substrate is 1.6 to 2.1 mg / cm 2 .

[0016] Furthermore, the current collector matrix is ​​made of aluminum foil or copper foil; the adhesive is made of PVDF, CMC / SBR, sodium polyacrylate or sodium alginate; and the conductive agent is made of conductive carbon black, SP, carbon nanotube CNT or graphene.

[0017] Beneficial effects: Compared with the prior art, the present invention provides a relatively simple preparation process flow of hard carbon negative electrode materials, which can further promote the commercialization of sodium ion batteries, improve sustainable energy applications, and promote the development of renewable energy. The hard carbon negative electrode material prepared by the present invention has excellent electrochemical properties, showing a reversible capacity of 313mAh / g at 0.1C, and can still achieve a capacity retention rate of 92% after 500 cycles at 1C (discharge) and 5C (charge). The prepared hard carbon even shows an excellent capacity of 209mAh / g at 10C. In addition, the assembled HC-1400||Na3V2(PO4)3 full battery also shows a high energy density of 204.4Wh / kg at 0.5C, and even at a high rate of 10C, it still shows 116.6Wh / kg. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a light microscopic image of the Paulownia xylem in Example 3 of the present invention.

[0019] Figure 2 This is the first charge and discharge curve diagram of the hard carbon negative electrode material of Examples 1 to 3 of the present invention.

[0020] Figure 3 This is a rate performance diagram of the hard carbon negative electrode materials of Examples 1 to 3 of the present invention at different current densities.

[0021] Figure 4 This is a cycle performance diagram of the hard carbon negative electrode material of Examples 1 to 3 of the present invention.

[0022] Figure 5 This is a cycle performance diagram of a full battery assembled with the hard carbon negative electrode material of Example 3 of the present invention and the Na3V2(PO4)3 positive electrode. DETAILED DESCRIPTION

[0023] The present invention is further explained below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. After reading the present invention, various equivalent forms of modifications to the present invention by those skilled in the art all fall within the scope defined by the claims attached to this application.

[0024] Example 1

[0025] The plant wood was crushed into powder with a crusher, then washed with deionized water and anhydrous ethanol for 5 times, and dried at 80°C for 12h. The dried precursor was divided into 5 equal parts, placed in a tube furnace, and pre-carbonized in an argon atmosphere (flow rate 0.2L / min), the pyrolysis temperature was controlled at 600°C, the heating rate was 5°C / min, and the temperature was kept for 2 hours, then heated to 1000°C at the same heating rate, and kept at 1000°C for 2 hours. The obtained hard carbon sample was washed with an excess of 1mol / LHCl solution and a certain amount of deionized water to remove impurities, and then dried at 100°C for 12h to obtain a hard carbon negative electrode material. The product was named HC-1000, and its half-cell first discharge capacity was 239.7mAh / g, and the first discharge efficiency was 76.8%.

[0026] Example 2

[0027] The plant xylem was crushed into powder with a crusher, washed with deionized water and anhydrous ethanol 5 times, and then dried at 80°C for 12h. The dried precursor was divided into 5 equal parts and placed in a tubular furnace. In an argon atmosphere (flow rate 0.2L / min), carbonization was carried out at 600°C for 2 hours at a heating rate of 5°C / min, then heated to 1200°C at the same heating rate and kept at 1200°C for 2 hours. The obtained hard carbon sample was washed with an excess of 1mol / L HCl solution and a certain amount of deionized water to remove impurities, and then dried at 100°C for 12h to obtain a hard carbon negative electrode material. The product was named HC-1200, and its half-cell first discharge capacity was 291.2mAh / g, and the first discharge efficiency was 81.8%.

[0028] Example 3

[0029] The plant xylem was crushed into powder with a crusher, washed with deionized water and anhydrous ethanol for 5 times, and then dried at 80°C for 12h. The dried precursor was divided into 5 equal parts and placed in a tube furnace. In an argon atmosphere (flow rate 0.2L / min), carbonization was carried out at 600°C for 2 hours at a heating rate of 5°C / min, and then heated to 1400°C at the same heating rate and kept at 1400°C for 2 hours. The obtained hard carbon sample was washed with an excess of 1mol / L HCl solution and a certain amount of deionized water to remove impurities, and then dried at 100°C for 12h to obtain a hard carbon negative electrode material. The product was named HC-1400, and its half-cell first discharge capacity was 313mAh / g, and the first discharge efficiency was 85.9%. The capacity retention rate of the full battery after 100 cycles at 1C was 83.7%.

[0030] Example Performance Testing

[0031] (1) The hard carbon layer spacing d of the hard carbon negative electrode materials in Examples 1 to 3 was respectively 002 , graphitization degree IG / ID, average nanographite domain length (La) and thickness (Lc), number of stacked graphene sheets (N), specific surface area, micropore volume test and calculation, the results are listed in Table 1. Interlayer spacing d 002 It can be obtained by powder XRD analysis using the Scherrer equation: The average nanographite domain length (La) and thickness (Lc) are calculated. The K values ​​of the (100) and (002) peaks of the carbon material are 1.84 and 0.90, respectively. λ is the XRD incident wavelength. Where β is the full width at half maximum of the peak. The number of stacked graphene sheets (N) can be obtained as N = Lc / d002. The specific surface area and pore structure of the prepared hard carbon negative electrode material were evaluated by CO2 adsorption-desorption measurements (using Brunauer-Emmett-Teller (BET) and density functional theory (DFT) calculations).

[0032] Table 1

[0033]

[0034] Note: I D and I G is the integrated intensity of the D band and the G band, and mv is the abbreviation of micropore volume.

[0035] As can be seen from Table 1, the hard carbon material of the present invention has a lower micropore volume and specific surface area, obtains a lower SSA and reduces the formation of SEI, which is beneficial to improving ICE.

[0036] (2) The hard carbon negative electrode materials of Examples 1 to 3 were tested as follows using a half-cell test method:

[0037] ① Test of the first charge and discharge capacity and efficiency (attached Figure 2 ), some of the results are listed in Table 1.

[0038] ② Rate performance test at different current densities (Appendix Figure 3 )

[0039] ③ Cycle performance test (attached Figure 4 )The half-cell test method is: the hard carbon negative electrode material sample, carbon black and sodium alginate are ground into a slurry with a mass ratio of 8:1:1 and coated on the copper foil by blade coating. After vacuum drying, they are cut into electrode sheets with a diameter of 14 mm. The mass of active material in each sheet is controlled at 2-2.5 mg. All sample electrodes use sodium foil as the counter electrode. When the water oxygen content is less than 0.01 ppm, a 1M NaPF6 solution dissolved in diethylene glycol dimethyl ether is used as the electrolyte, and glass fiber (GF / A, Whatman) is used as the diaphragm. The 2032 button cell assembled in an argon-filled glove box was electrochemically tested on the LANDCT3002A battery testing system. The electrochemical test voltage window is 0-2V.

[0040] By the attached Figure 2 As can be seen from Table 1, compared with the first discharge capacity of 239.7 mAh / g (76.8%) of Example 1 and the first discharge capacity of 291.2 mAh / g (81.8%) of Example 2, the hard carbon negative electrode material of the present invention exhibits a high reversible capacity of 313 mAh / g and a high ICE of 85.9%.

[0041] By the attached Figure 3 It can be seen that due to the inheritance of the three-dimensional porous interconnected structure of the plant xylem, the diffusion path of sodium ions is greatly shortened, and the prepared material exhibits excellent high current retention capacity. In particular, the hard carbon negative electrode material of the present invention can still exhibit a reversible capacity of 209 mAh / g at 10C, which is much higher than the current commercial carbon. At the same time, the prepared hard carbon exhibits excellent cycle stability under 1C and 5C discharge charges.

[0042] By the attached Figure 4 It can be seen that the capacity retention rate of the hard carbon negative electrode material of the present invention after 500 cycles is as high as 92% (243 mAh / g), showing excellent long-cycle stability.

[0043] (3) The hard carbon negative electrode material of Example 3 was tested using a full battery test method. The full battery test method is: use the hard carbon negative electrode material of Example 3 as the negative electrode, and use Na3V2(PO4)3 as the positive electrode to assemble a full battery, the capacity ratio of the negative electrode to the positive electrode is 1.1-1.2, the operating voltage window is set to 2-3.8V, and the rate is set to 0.5-10C. A 1M NaPF6 solution dissolved in diethylene glycol dimethyl ether is used as the electrolyte, and glass fiber (GF / A, Whatman) is used as the separator. The capacity retention rate of the assembled full battery after 100 cycles at 1C is 83.7%, indicating good cycle performance. The results are as follows Figure 5 shown.

[0044] The above descriptions are only some embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a xylem-derived array-type through-hole structure hard carbon negative electrode material, characterized in that The following steps are involved: S1, after the plant xylem is crushed, it is washed to remove impurities and dried to obtain a hard carbon precursor; S2, under the protection of inert gas, heating the hard carbon precursor to 550-700°C for pre-carbonization treatment for 2-3 hours to obtain a xylem precursor, wherein the heating rate is 2-5°C / min; S3, under the protection of inert gas, the pre-carbonized wood precursor is further heated to 1000-1400°C and kept at high temperature for 1-3 hours to obtain an array pore structure hard carbon material after washing and drying, and the heating rate is 2-5°C / min.

2. According to claim 1, the method for preparing a xylem-derived array-type through-hole structure hard carbon negative electrode material is characterized by: In steps S1 and S2, high-purity argon is used as the inert gas with a flow rate of 0.2-0.4 L / min.

3. The method for preparing a xylem-derived array-type through-hole structure hard carbon negative electrode material according to claim 1, characterized in that: The plant wood is made of paulownia, sycamore, elm or maple.

4. According to claim 1, the method for preparing a xylem-derived array-type through-hole structure hard carbon negative electrode material is characterized by: The washing in step S1 is performed by alternately washing with deionized water and anhydrous ethanol for at least 3 times; the washing in step S3 is performed by alternately washing with 1 mol / L HCl solution and deionized water for at least 2 times.

5. The method for preparing a xylem-derived array-type through-hole structure hard carbon negative electrode material according to claim 1, characterized in that: The drying temperature in steps S1 and S3 is 70-85° C., and the drying time is at least 12 hours.

6. A method for preparing a negative electrode sheet for a sodium ion battery, characterized in that The method comprises the following steps: mixing the hard carbon negative electrode material prepared by any method described in any one of claims 1 to 5, an adhesive and a conductive agent in a mass ratio of 8:1:1, and grinding to form a paste slurry, applying the paste slurry on a current collector substrate by a doctor blade method, and vacuum drying at a temperature of 70 to 120°C for 1 to 6 hours.

7. The method for preparing a negative electrode sheet for a sodium ion battery according to claim 6, characterized in that: The coating amount of the paste slurry on the current collector substrate is 1.6-2.1 mg / cm 2 .

8. The method for preparing a negative electrode sheet for a sodium ion battery according to claim 6, characterized in that: The current collector matrix is ​​made of aluminum foil or copper foil; the adhesive is made of PVDF, CMC / SBR, sodium polyacrylate or sodium alginate; and the conductive agent is made of conductive carbon black, SP, carbon nanotube CNT or graphene.

Citation Information

Patent Citations

  • Composite hard carbon negative electrode material, and preparation method and application thereof

    CN103311519A

  • Pyrolyzed hard carbon material, preparation and its applications

    CN1422235A

  • Sodium-ion battery carbon negative electrode material prepared based on waste wood chips and preparation method thereof

    CN113651307A

  • Lignin-based hard carbon composite material and application thereof in lithium ion battery negative electrode material

    CN116646495A

  • Method for preparing sodium-ion battery carbon-based negative electrode material from waste wood

    CN119059511A